Shaping Self-Disciplined Workers: A Study of Silent Power in HRD - Vicki K. Carter; Sharon L. Howell; Fred M. Schied (Adult Education Research Conference, 1999)
The intent of this case study was to examine power theories in a singular HRD context in such a way that problematizes the consequences of power.